Preliminary study of electromagnetic energy absorption in the head due to the exposure of radio frequency at 900MHz - Mohd Hafizuddin, Mat (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org